(untitled) (Journal of Contemporary Studies, 2018)
Abstract The study aims to explore the dissemination of hate messages and intolerant discourses in religious publications from religious seminaries originating in three key districts of the Punjab province, namely Lahore, Multan and Bahawalpur. After a thorough examination, twelve publications were selected for study and to see if they incite readers on taking extreme positions against those hailing from other sects and religions. Framing theory was employed to study various types of frames embedded in the form of hate content in religious publications. While using this theory, the study found six different frames: inter-religious hatred, sectarian hatred, criticism of mainstream media, gender bias, criticism of educational institutions, and criticism of civil society. This study confirms that there is a pattern in religious publications to have a significant amount of content, reflecting hate and discrimination based on religion and sect. However, not all religious publications incite hatred; a majority are sources of information, propagating their beliefs based on their own sectarian identity and preferences.